THE ROLE OF EXTRACURRICULAR ACTIVITIES, PERSONALITY AND SOCIAL INFLUENCES IN CAREER EXPLORATION AND DECISION-MAKING OF TWELFTH-GRADE STUDENTS - Ştefana BUHĂESCU-CIUCĂ (National Centre for Policy and Evaluation in Education, 2023)
The present study is testing the role of extracurricular activities in the career exploratory intentions and decision-making using the lenses of the career self-management model of Social Cognitive Career Theory - SCCT (Lent & Brown, 2013). The study also includes the socioeconomic status, social support, and role models, as well as personality factors as predictors. We used hierarchical linear regression to test the role of the added precursors to extracurricular activities and their role in career exploration goals and decidedness. Data were collected using an online survey filled in by 233 students in twelfth grade. Involvement in pro-social activities, the influence of role models, and the level of agreeableness were significant predictors of exploratory intentions while exam preparation was the only significant predictor of career decidedness. Implications for practice are discussed.